2009
DOI: 10.1007/s11999-008-0643-3
|View full text |Cite
|
Sign up to set email alerts
|

Pedicled Fasciocutaneous Flap of Multi-island Design for Large Sacral Defects

Abstract: We designed a new pedicled fasciocutaneous flap for large sacral defects that combined a classic superior gluteal artery perforator flap and an acentric axis perforator pedicled propeller flap. We asked whether this technique would be simple and result in few complications. Six patients with large sacral defects had reconstruction using this technique in one stage. The size of the defect and postoperative complications in each patient were assessed. The minimum followup was 6 months (mean, 20.1 months; range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…30,31 While they continue to be a preferable option for decubitus ulcers, breast reconstruction, and pilonidal sinus disease, modifications of the GAP flaps have recently been adopted for reconstructing more extensive sacral defects created by oncologic resection. [32][33][34][35] Additional flaps are sometimes required for more extensive defects which may not be amenable with a single flap. In our cohort, two patients had an omental flap and one had a gluteal flap in addition to their VRAM flaps.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 While they continue to be a preferable option for decubitus ulcers, breast reconstruction, and pilonidal sinus disease, modifications of the GAP flaps have recently been adopted for reconstructing more extensive sacral defects created by oncologic resection. [32][33][34][35] Additional flaps are sometimes required for more extensive defects which may not be amenable with a single flap. In our cohort, two patients had an omental flap and one had a gluteal flap in addition to their VRAM flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Debridement of pressure sores often results in extensive soft tissue defects that cannot be closed primarily and are further associated with increased risk of flap ischemia, wound dehiscence, and deep infection [12]. Numeral surgical methods have been used to correct these defects, including skin grafting [12, 13], local flaps [12, 14], muscle flaps [12, 15], and free flaps [12, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Numeral surgical methods have been used to correct these defects, including skin grafting [12, 13], local flaps [12, 14], muscle flaps [12, 15], and free flaps [12, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Koshima I, et al, [20] reported that in eight pressure ulcers treated with gluteal perforator flaps, one fistula occurred. Lin PY, et al, [21] identified one seroma in 46 gluteal perforator flaps; Xu Y, et al, [22] also noted one seroma among six flaps. Leow M, et al, [23] reported four successful gluteal perforator flap surgeries without seroma formation.…”
Section: Discussionmentioning
confidence: 99%